Orographic precipitation model for hydrometeorological use - Rhea, J. Owen, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1978)
Research was performed to determine the ability to diagnose the effect of topography on winter precipitation for western Colorado over various time periods for differing wind regimes, employing upper air data and a fine-mesh topographic grid. To accomplish the objectives, a simple, operationally-oriented orographic precipitation model was developed. The model is two-dimensional, steady state, and multi-layer. It follows parcels at layer mid-points through topographically-induced moist adiabatic ascents and descents. Layer budgets of water substance are calculated by (a) allowing precipitation of a constant fraction of total cloud water (i.e., local condensation plus imported cloud water), (b) carrying the remainder downstream where it and additional condensate can partially precipitate, and (c)permitting evaporation of cloud water upon descent and of precipitation falling into subsaturated layers. A key feature of this approach is its representation of precipitation shadowing by upstream barriers (when used with a different topographic grid for each wind direction). Airflow is constrained to two dimensions and the complications of topographic effects on the flow are minimized by using a set of stability-dependent damping factors to adjust the vertical displacement of layers. Effects of large-scale vertical motion are added to those of topography. The model was tested for western Colorado using 13 winter seasons of twice daily upper air measurements as input. Results were summed and compared to observed spring and summer runoff from watersheds of varying size. Correlation coefficients between seasonally-summed model watershed precipitation and observed runoff range mainly between 0.75 and 0.94. On a daily basis large discrepancies between model and observation sometimes exist, but model frequency distribution of daily precipitation totals appears realistic. A 13 year model mean precipitation map was found to agree quite well in mountainous areas with an isohyetal map constructed by ESSA of the U.S. Department of Commerce using precipitation and snow-course data with empirical correlation to topographic features. The model underestimated broad valley precipitation in most cases. Test quantitative precipitation forecasts (QPF's) were made (and communicated daily to the U.S. Forest Service) from November, 1975 to March, 1976 using wind direction-dependent model pattern maps as objective aids. Isohyets on these pattern maps were calibrated using forecast wind speed, moisture depth, duration, areal coverage, and cloud temperature. Skill scores for 24 hour QPF's ranged from 0.56 to 0.87. The derived method has utility (a) in assessing the average magnitude and the inter-season variation of topographic effects on winter precipitation in western Colorado and (b) as an objective aid for quantitative precipitation forecasting. It has substantial potential utility as input to hydrologic process models for streamflow forecasting. The basic approach should be transferable to other topographically complex areas which are dominated by stratiform precipitation.
March 1978.
Keywords: Precipitation (Meteorology) -- Mathematical models; Weather -- Effect of mountains on -- Colorado